NILAI-NILAI BUSHIDO DALAM MINWA - Yuliani Rahmah (KIRYOKU, 2018)
(Title:The values of Bushido in Minwa) Minwa is one of the collective culture of Japanese society that is used also as a method to teached the values and norms of the society. This paper explains about the values and norms of life of traditional Japanese society in particular the values of bushido. In addition to the generally illustrated life values, Minwa’s story filed with Bushido values. Those values can seen in the character's behavior, the series of events and the background of the community in the story . Of the three types of minwa, this research is used is Densetsu and Mukashi banashi as the object of research. From the analysis of those two types of minwa, it can be seen that 7 main values of Bushido ( Gi,Yu,Jin,Mei,Meiyo,Chuugi, Makoto) reflected on Densetsu and mukashibanashi intrinsic unsure. Keywords :Bushido values;Minwa ; Folklore